PERSEPSI MASYARAKAT DALAM MENGIKUTI PROGRAM KELUARGA BERENCANA DI DESA RENGGARASI KECAMATAN TANAWAWO KABUPATEN SIKKA - Lale, Silvia Nona Arnaldina; Samin, Mikael; Hasan, Muhammad Husain (Jurnal Geografi, 2021)
The aims of this research were: (1) To find out the community's perception of the family planning program in Renggarasi Village, Tanawawo District, Sikka Regency, (2) To find out the things behind the community in participating in the family planning program in Renggarasi Village, Tanawawo District, Sikka Regency, (3 ) To find out the types of contraceptives used by people of Renggarasi Village, Tanawawo District, Sikka Regency. This study used a descriptive method with a qualitative approach. Sources of research data were informants and documents and archives, data collection techniques were interviews and reviewing documents, data analysis used data reduction, data presentation and verificatin. The results of this study were: (1) Public perceptions of family planning programs were that family planning was a woman's obligation, family planning was only done using contraceptives, and some contraceptives were scary for the acceptors. (2) The community's background in participating in the family planning program was for economic reasons and health reasons. (3) The types of contraceptives used by the community are injections, implants and condoms.